Variability for drought resistance on the growth and yield of five selected cultivars of cassava (Manihot esculenta) in Ekiti State, Nigeria (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
Field experiments were conducted using five selected cassava cultivars in 2014 and 2015 years at the Teaching and Research Farm, Federal University Oye, Ekiti State, Nigeria to determine variability for drought resistance among five cassava cultivars through estimating heritability of yield and yield components, genetic advance, correlation coefficients of yield contributing traits. The experiments were conducted as a Randomized Complete Block Design (RCBD) with three replications. Twelve competitive plants were selected from the middle row of plots for data collection. Data collected include plant height (cm), stem girth (cm), number of leaves, number of branches/plant, average number of tuber/plant, average tuber length, total tuber weight/plant and yield/ha. Slight to high differences were observed between the Phenotypic Coefficient of Variation (PCV) and Genotypic Coefficient of Variation (GCV). Phenotypic variances for the characters under study were higher than genotypic variances in the years, indicating high influence of the environment which allows for the selection of character combinations and pools for genetic gain. This study revealed that indigenous cassava (Manihot esculenta) cultivars used in this experiment showed better growth responses in dry weather conditions, an indication that the cultivars posses some strains in their genetic constitution that may be useful in developing improved drought resistant varieties of cassava.Asian Australas. J. Biosci. Biotechnol. 2017, 2 (2), 145-153